2008
DOI: 10.1074/jbc.m802206200
|View full text |Cite
|
Sign up to set email alerts
|

Regiospecific O-Methylation of Naphthoic Acids Catalyzed by NcsB1, an O-Methyltransferase Involved in the Biosynthesis of the Enediyne Antitumor Antibiotic Neocarzinostatin

Abstract: Neocarzinostatin, a clinical anticancer drug, is the archetypal member of the chromoprotein family of enediyne antitumor antibiotics that are composed of a nonprotein chromophore and an apoprotein. The neocarzinostatin chromophore consists of a nine-membered enediyne core, a deoxyaminosugar, and a naphthoic acid moiety. We have previously cloned and sequenced the neocarzinostatin biosynthetic gene cluster and proposed that the biosynthesis of the naphthoic acid moiety and its incorporation into the neocarzinos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 44 publications
3
21
0
Order By: Relevance
“…Similar aromatic polyketide moieties have been found in other enediyne natural products, as exemplified by the benzoic acid moiety in MDP and the 1-naphthoic acid moiety in NCS, and the biosynthesis of both moieties are catalyzed by the iterative type I PKSs, MdpB 26,52 and NcsB, 25,4951 respectively (Fig. S7).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Similar aromatic polyketide moieties have been found in other enediyne natural products, as exemplified by the benzoic acid moiety in MDP and the 1-naphthoic acid moiety in NCS, and the biosynthesis of both moieties are catalyzed by the iterative type I PKSs, MdpB 26,52 and NcsB, 25,4951 respectively (Fig. S7).…”
Section: Discussionsupporting
confidence: 66%
“…S7). 25,26,4951 These findings lend additional support to the intermediacy of 3,6,8-trihydroxy-2-naphthoic acid in KED biosynthesis. Thus, as depicted in Fig.…”
Section: Discussionmentioning
confidence: 53%
“…The LDXGXGXG motif indicative of SAM-utilizing proteins is found in NcsB1 as VDVGGGSG and is located between β3 and α14. We previously reported that NcsB1 alkylates the substrate 3 with a variety of SAM analogs, including S -ethyl and S -n-propyl, to the corresponding 7-alkyl ether with reasonable efficiency (21). The nearest side chain to the methyl-group on SAM is the sterically small Ala243 (3.5 Å distance).…”
Section: Resultsmentioning
confidence: 99%
“…NcsB1 also was demonstrated to methylate 1,4-dihydroxy-2-naphthoic acid (see Figure 5, 6) at the 4-hydroxyl group, which was surprising because of the large difference in the location of the reactive hydroxyl group from that on the natural substrate, necessitating a reorientation of the substrate in the active site. This observation led to the prediction of a model by which naphthoic acids flexibly bind the active site, and that the 1,2-hydroxy acid functionality was required for substrate binding and SAM-dependant methylation (21). …”
mentioning
confidence: 99%
“…Particular interest surrounds the mammalian O -methyltransferases (OMTs) as they are the targets of therapeutic agents designed to treat Parkinson's disease 2. More recently, OMTs have attracted considerable interest on account of their roles in decorating antibiotics3; 4;5 and other therapeutic agents6 and their potential application for creating chemical diversity in a range of compound classes.…”
Section: Introductionmentioning
confidence: 99%